Marine propellers and propulsion - Carlton, J. S. (John S.) (Butterworth-Heinemann, 2012)
Propulsion technology is a complex, multidisciplinary topic with design, construction, operational and research implications. Bringing together a wealth of disparate information from the field, Marine Propellers and Propulsion provides comprehensive and cutting edge coverage to equip marine engineers, naval architects and anyone involved in propulsion and hydrodynamics with the knowledge needed to do the job. Drawing on experience from a long and varied career in consultancy, research, design and technical investigation, author John Carlton breaks the subject into three main sections-hydrodynamic theory, materials and mechanical considerations, and design, operation and performance. Connecting essential theory to practical problems in design, analysis and operational efficiency, Marine Propellers and Propulsion is an invaluable resource, packed with hard-won insights, detailed specifications and data. The most complete book available on marine propellers, fully updated and revised, with new chapters on propulsion in ice and high speed propellers.Gathers together otherwise disparate material on the theory and practice of propulsion technology from the past 40 years' development, including the latest developments in improving efficiency.Written by a leading expert on propeller technology, essential for students, marine engineers and naval architects involved in propulsion and hydrodynamics.